The extent of Appropriateness of the school environment within Nablus Directorate for development of talented students at Lower Basic Schools from their teachers' point of view - Sholi, Fayha AbdAlSalam Ahmed (Journal of Educational and Psychological Sciences, 2023)
This Study aims to identify the extent of Appropriateness of the school environment within Nablus Directorate for the development of talented students at Lower Basic Schools from their teachers' point of view. The researcher adopts the descriptive analytical approach. The sample of the Study consists of (88) teachers of both sexes out of Primary School Teachers. A questionnaire, consisting of (39) items, was distributed to cover three fields: Physical Environment, Administration & Teachers along with Curricula and Teaching methods. The results of the study show that the extent of the Appropriateness of the school environment within Nablus Directorate for the development of talented students at Lower Basic Schools from their teachers' point of view was moderate with arithmetic mean: (3.22). Curricula and teaching methods occupy the First Rank with an arithmetic mean of (3.51) greatly. Physical Environment takes over the Second Rank with an arithmetic mean of (3.11). Administration and Teachers are in the third place as: (2.99) with a moderate degree. There are statistically significant differences in the total average of responses gathered for this study within samples due to the variables of gender, academic qualification and years of experience. The researcher recommends the need to provide schools with scientific laboratories equipped with the necessary tools, devices and materials, and the need to urge officials in the Ministry of Education to visit schools in which gifted students are present.
Keywords: School Environment; Talented Students; Lower Basic Stage; Nablus Directorate of Education